(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The study deals with green manufacturing, which is relevant because of how necessary it is and the many ways it cuts down on waste and pollution. The paper focus on the origin and overview of green manufacturing, green manufacturing defined, importance of green manufacturing, types of green manufacturing technologies, operational technologies, green manufacturing tools, strategie green manufacturing, green manufacturing practices, green manufacturing trends, cases, experience, green manufacturing organisational culture, green manufacturing measurement, companies implementing green technologies.